Biomechanically and Periodontally-Based Orthodontic Treatment of a Patient with Upper Canine Affected by External Cervical Resorption (ECR): A Case Report - Marino Musilli; Morena Tina Iuorio; Emanuele Vaia; Enzo Vaia; Luca Ramaglia; Vincenzo D'Antò (MDPI AG, 2023)
(1) Background: Orthodontic treatment may be a potential predisposing factor for ECR. The affected tooth goes to ankylosis, which could lead to a malocclusion. Although teeth severely affected by ECR (class IV Heithersay) are usually extracted, this case report aims to present the use of an ECR class IV upper canine, both as ankylosed to solve the malocclusion and the occlusal plane canting, as well as not ankylosed to correct its ridge defect with orthodontic extrusion. (2) Methods: A 14-year-old male, complaining of an ugly smile and a failed orthodontic attempt to recover an impacted canine, was referred to the orthodontic clinic. He was diagnosed with class II right subdivision, midline deviation, both upper and lower occlusal plane canting, and an upper left canine, previously impacted, showing ECR class IV. The treatment first included canting resolution with a cantilever and a spring, exploiting the anchorage offered by the ankylosed ECR canine. Then, a coronectomy, endodontic treatment, and orthodontic extrusion of that canine were performed to obtain the implant site development. (3) Results: Clinical and radiographic outcomes showed normocclusion and better bony conditions for safer implant placement in the aesthetic zone. (4) Conclusions: The high aesthetics and the periodontal and bony conditions obtained are probably not achievable by other therapeutic alternatives.